1993
DOI: 10.1111/j.1651-2227.1993.tb12906.x
|View full text |Cite
|
Sign up to set email alerts
|

Early child health in Lahore, Pakistan: V. Feeding patterns

Abstract: The feeding practices of children (n = 1476) from birth to 24 months, as determined in a longitudinal study, in Lahore, Pakistan, are presented. Four socioeconomic groups at various levels of urbanization were included; a village, periurban slum, urban slum and an upper middle class. Initiation of breastfeeding was delayed in all the neonates. Sixty-five percent of the periurban slum mothers and 45% of the village mothers had not started breastfeeding at 48 hours after the birth of the infant. Prelacteal feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…Commercial Ghutti is now available on the market. The traditional and/or ceremonial foods that may be given, in place of colostrum, for example honey, rosewater, or cardamom water have a high potential for contamination (Ashraf et al, 1993) and may be described as 'risky feeding practices' (Fikree et al, 2005, p. 911). From the focus group data following the health promotion programme it appears that, based on the perceptions of the LHWs, women's understanding did change to their recognition that exclusive breast feeding for 6 months was the optimum.…”
Section: Discussionmentioning
confidence: 98%
“…Commercial Ghutti is now available on the market. The traditional and/or ceremonial foods that may be given, in place of colostrum, for example honey, rosewater, or cardamom water have a high potential for contamination (Ashraf et al, 1993) and may be described as 'risky feeding practices' (Fikree et al, 2005, p. 911). From the focus group data following the health promotion programme it appears that, based on the perceptions of the LHWs, women's understanding did change to their recognition that exclusive breast feeding for 6 months was the optimum.…”
Section: Discussionmentioning
confidence: 98%
“…Otherwise delay in initiation and discarding of colostrum was observed more in rural than in urban areas 23,24,27,30,31 . Other studies have suggested that prelacteal feeds are given to infants in both rural and urban areas 7,20,27,32 except in Sudan, where breast milk was given as the first feed to a higher proportion of infants in the urban areas than in the rural ones 8 . The proportion of infants less than 4 months of age who were fully breastfed in 17 studied countries in sub-Saharan Africa was higher in the rural areas than in the urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings from other studies have been reported to be associated with increased incidence of hypothermia, diarrhoea, and acute respiratory tract infections in infants who are not exclusively breast fed. [25][26][27] It is known that Zambian mothers in general breast feed for long periods, but little is known about the details of the breast feeding behaviour, or the type and use of supplementary and weaning foods in urban mothers. 28 A major problem among the newborns during the first weeks of life was eye infection and this was identified both by the mother and the midwife.…”
Section: Discussionmentioning
confidence: 99%